P-317 Impact of Musashi-1 and Musashi-2 double knockdown on Notch signaling and the pathogenesis of endometriosis. (30th June 2022) - Strauß, T; Greve, B; Gabriel, M; Kiesel, L; Poutanen, M; Schäfer, S.D; Götte, M
Abstract: Study question: Do Musashi proteins mechanistically contribute to the pathogenetic properties of endometriotic cells? Summary answer: Silencing of Musashi-1 and Muashi-2 reduces the expression of stemness-related genes, inhibits spheroid growth and viability, and increases apoptosis in endometriotic cells. What is known already: Putative stem cells expressing the RNA binding protein Musashi-1 are more frequent in endometriotic lesions compared to healthy secretory endoemtrium. Musashi-1 is a positive regulator of the stemness-associated notch signaling pathway. Loss of Musashi-1 and Musashi-2 function in breast and ovarian cancer cells is associated with increased apoptosis and reduced cell viability. Study design, size, duration: In vitro laboratory study on an immortalized endometriotic cell line (12Z) and primary endometriotic stroma cells (N > 3 replicates). Gene expression analysis utilizing the Endomet Turku Endometriosis database (82 samples of healthy tissue and 576 samples of endometriotic tissue). Participants/materials, setting, methods: Gene expression associated with notch signaling pathway and stem cell function was analysed in tissue samples of 82 healthy controls and 576 endometriosis patients from the Endomet Turku Endometriosis database. In vitro studies were performed using siRNA double-knockdown of Muashi-1 and Musashi-2 in the endometriotic cell line 12Z and primary endometriotic stroma cells derived from ectopic lesions of two patients.Cell viability, apoptosis, sphere formation and gene expression (qPCR/Flow cytometriy) were studied in vitro . Main results and the role of chance: The expression of Musashi genes and Notch signaling are dysregulated in patients with endometriosis (p < 0.05). Musashi-double-knockdown increased the apoptosis and necrosis rate as determined by flow cytometry (p < 0.05). Cell viability is significantly reduced in MTT assays (p < 0.05). Musashi knockdown reduces the side population and ALDH activity in endometriotic cells (p < 0.05), and reeuces the size of spheroids formed ina hanging drop assay (p < 0.05).. Musashi-double-knockdown leads to a downregulation of stem cell gene expression, including a downregulation of Notch-2 and Hes-1, as confirmed at the protein level by flow cytometry (p < 0.05). Limitations, reasons for caution: Our gene expression study is based on a single patient collective and has not been confirmed in an independent cohort. The in vitro study is partially based on an immortalised cell line. siRNA transfection may have caused toxic side effects.Studies on endometriotic cells only do not address the lesion microenvironment, Wider implications of the findings: The Musashi genes have an impact on Notch signaling and the pathogenesis of endometriosis through dthe reduction of proliferation and stemness characteristics and upregulation of apoptosis and necrosis. A targeting of the Muashi-Notch axis may be a therapeutic concept worth evaluating. Trial registration number: not applicable